A New Computational Technique Design for EMHD Nanofluid Flow Over a Variable Thickness Surface With Variable Liquid Characteristics - Irfan, Muhammad; Farooq, Muhammad Asif; Iqra, Tousif (Frontiers in Physics, 2020)
The objective of paper comprises two key points: descriptive mathematical model for constant and variable fluid flows over a variable thickness sheet by inducting applied electric and magnetic fields, porosity, radiative heat transfer, heat generation/absorption and seeking their solution by constructing a novel numerical method, the Simplified Finite Difference Method (SFDM). We resort to similarity transformations to implicate partial differential equations (PDEs) into a set of ordinary differential equations (ODEs). Optimal results for a pair of ODEs obtained from SFDM are assessed by drawing a comparison with bvp4c and existing literature values. SFDM has been implemented in MATLAB for both constant and variable fluid properties. Tabulated numerical values of the skin friction coefficient, local Nusselt and Sherwood numbers are measured and analyzed against different parameters. Influence of distinct parameters on velocity, temperature, and nanoparticles volume fraction have been explained in great detail via diagrams. The skin friction coefficient for variable fluid properties is greater than the constant fluid properties. However, the local Nusselt number is less for variable fluid properties when compare with constant fluid properties. Surprisingly, the high precision computational results are achieved from the SFDM.